2022
DOI: 10.3390/plants12010103
|View full text |Cite
|
Sign up to set email alerts
|

The Phenolic Profile of Sweet Cherry Fruits Influenced by Cultivar/Rootstock Combination

Abstract: The influence of three cultivars (‘Carmen’, ‘Kordia’ and ‘Regina’) grafted on six rootstocks (Mahaleb, ‘Colt’, ‘Oblacinska’, ‘M × M 14′, ‘Gisela 5′ and ‘Gisela 6′) on the phenolic profile of sweet cherry fruits was studied during a two-year period. All the individual phenolic compounds were detected using high-pressure liquid chromatography with diode-array detection coupled with mass spectrometry (HPLC-DAD-MSn). In all the examined samples, 54 compounds were identified and divided into five phenolic classes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Grafting is a traditional technique of asexual propagation since antiquity for fruit crop improvement, and has been widely used in many horticultural crops, such as apple [ 1 , 2 ], pear [ 3 , 4 ], citrus [ 5 ], and grape [ 6 ]. Certain rootstocks not only affect the adaptability of fruit trees to the natural environment, but also influence tree growth potential and fruit production efficacy [ 7 ]. Numerous studies have demonstrated that dwarf rootstocks could be advantageous for shoot dwarfing to benefit mechanized operations and increase the fruit yield per unit area, and could also enhance fruit crop resistance to abiotic and biotic stresses [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grafting is a traditional technique of asexual propagation since antiquity for fruit crop improvement, and has been widely used in many horticultural crops, such as apple [ 1 , 2 ], pear [ 3 , 4 ], citrus [ 5 ], and grape [ 6 ]. Certain rootstocks not only affect the adaptability of fruit trees to the natural environment, but also influence tree growth potential and fruit production efficacy [ 7 ]. Numerous studies have demonstrated that dwarf rootstocks could be advantageous for shoot dwarfing to benefit mechanized operations and increase the fruit yield per unit area, and could also enhance fruit crop resistance to abiotic and biotic stresses [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%